Challenges Encountered by the Teachers Handling Oral Speech Communication Courses in the Era of Covid-19 Pandemic - Gula, Louie Petere (JOLLT Journal of Languages and Language Teaching, 2022)
The fundamental reason for this survey is to point out the challenges encountered by the teachers, students, schools, and parents in facing and handling the oral communication subject during the pandemic. Given that, most of the medium of instruction we are using now is distance learning, it poses issues and concerns on how our respondents dealt with the situation. A descriptive- survey research design was being utilized to document the behavior, demographics, and experiences of the respondents correlated to the questions provided. The questionnaire includes questions that seek to gather information on their basic profile, current experiences, and behavior towards the problem. Therefore, I have narrowed down the different problems encountered by the teachers, students, school, and parents based on the responses I have collected. Some respondents answered the same problem encountered that leads to the validity of the issue. Most of the teachers encountered the problem of the students with lack of motivation which is indeed a very complicated problem because it deals with emotional readiness and stability. The students’ side of encountering a problem is the difficulty in comprehending the topics of the module because lessons are not explained personally by the teachers.